Identification of a pro-angiogenic functional role for FSP1-positive fibroblast subtype in wound healing - Sarika Saraswati (Nature Portfolio, 2019)
Activated fibroblasts are key contributors to tissue repair after cardiac injury. Here, Saraswati et al. identify and characterize a subpopulation of FSP1-positive cardiac fibroblasts with proangiogenic properties in infarcted hearts.